Possibilities of integrated secondary schooling considering the public funding of education (Educação e Pesquisa, 2009)
Taking as its reference the trajectory of secondary education in Brazil during the last 16 years, this work focuses on the impacts of limitations in public funding to the construction of an integrated secondary school system. Drawing from a literature on secondary and professional education that defends a unitary school, the article analyzes data related to the last stage of basic education, particularly in schools of the state system. It argues that the intervention of the Brazilian federal government in the funding of education constitutes a huge obstacle to the implementation of an integrated secondary school, since regardless of any ideological bias or party allegiance on the part of those governing the nation, this stage of education has not been considered as a priority for state funding. The work observes the hegemony of state schools in the offer of secondary education, and the increase in the number of schools in which there is integration between secondary schooling and professional education. Lastly, the text notes that, although FUNDEB represents an initiative that places secondary education as a candidate for state funding, it will not produce enough resources to guarantee the funding of the last stage of basic education, especially in a modality integrated to professional training. It concludes by defending a modification of the role played by the federal government in the funding of secondary education, so as to guarantee that the articulation between technical training and general education can be universalized, and with better quality, throughout state schools.